PENGARUH KUALITAS PELAYANAN PRAMUWISATA LOKAL TERHADAP KEPUASAN WISATAWAN NUSANTARA DI PURA LUHUR ULUWATU - Bulu, Stevania Hendrika; Sudana, I Putu; Kristianto, Yohanes (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2023)
The quality of local tour guide services is a factor in consideration of tourist satisfaction when visiting a tourist attraction. This study aims to determine the effect of the quality of local guide services on the satisfaction of domestic tourists at Luhur Uluwatu Temple. The operational definitions of the variables used in this study are service quality (X) and tourist satisfaction (Y). The sampling technique in this study was taken by accidental sampling with a total of 100 respondents. The respondents of this study were domestic tourists who used the services of local tour guides in tourist areas outside the Uluwatu sublime temple. While this research is descriptive quantitative using simple linear regression analysis as a data analysis technique. In this study using data collection techniques, namely observation, literature study, questionnaires, interviews, and distributing questionnaires to obtain data. The results of a simple linear regression analysis through partial testing of the effect of variable X on Y in table 4.30 produce F count = 29,270 at a significance of 0.001 T table 1,984 at a significance of 0.001 <0.005, so that it can be said that there is a positive and significant influence between the quality of local tour guide services on the satisfaction of domestic tourists at Pura Luhur Uluwatu. E. Keywords: service quality, local guides, tourist satisfaction, domestic touris